VOCABULARY WEALTH OF THE RUSSIAN LANGUAGE: SYNONYMS AND ANTONYMS OF MODERN SPEECH - Рафикжанова Шахноза Ровшан кизи (Bright Mind Publishing, 2025)
The Russian language is one of the richest and most expressive languages in the world, and its lexical diversity serves as the basis for the accurate and vivid transmission of ideas, emotions and cultural concepts. One of the most important aspects reflecting this richness is synonyms and antonyms, which play a significant role in modern speech. Synonyms and antonyms help to create ambiguity, enhance expression, emphasize contrasts and add emotional coloring to the language. The role of synonyms and antonyms in the Russian language, their functions and importance for communication is considered, and their dynamics in the context of modern changes in society and language practice is investigated.
Keywords: Lexical richness, synonyms, antonyms, modern speech, Russian language, language dynamics, functional features